Financial Crisis and Current Situation in Global Economy - Ďurkovič, Daniel (2008)
The goal of the thesis will be to describe the key elements of the economy and its infection by the crisis. It will give an insight on the typology of the crises and today's turmoil in the economic environment. It will try to estimate the impact of the crisis on Slovakia and forecast the development of its national debt